Experimental study of two-stage vertical axis hydrofoil water turbine NACA 64-212 with variation of blades number. Issue 6 (March 2021) - Fadlil, M F; Fahruddin, A; Akbar, A
Abstract: Efforts to utilize the potential energy sources of water flow for electricity generation generally using water turbines. One of them is the hydrofoil turbine which can work without any water head, by utilizing the speed of the river flow. This study aims to determine the power and efficiency generated by a prototype hydrofoil water turbine with a multi-stage installation. This experiment used a hydrofoil turbine with NACA 64-212 standard with variations in the number of blades: 4, 5, and 6 blades on the second stage. The experimental results show that the highest total power is 2.5 Watt at the number of blades 6 at a water discharge of 0.057 m3/s. While the greatest efficiency produced was 7.47% with the number of blades 6 at a water discharge of 0.036 m3/s.